DIALEKTIKA INKLUSIVISME DAN EKSKLUSIVISME ISLAM KAJIAN SEMANTIK TERHADAP TAFSIR AL-QURAN TENTANG HUBUNGAN ANTARAGAMA - Rofiq Nurhadi; Syamsul Hadi; Thoyib I. M.; Suhandano Suhandano (Universitas Gadjah Mada, 2013)
Potentially, both inclusivism and exclusivism can emerge from Islam itself. To an extreme point, inclusive point of view underline the importance to apprecieate religious pluralism and to avoid truth claims. To the other extreme, exlusive point of view suspect and even reject pluralism and upholds truth claims. Islam may be presented by the two extremes, and it is not only because of defferent emphasis in reading the holy texts, but also because of defferent methodologies of interpretation being employed. This paper discusses different methodologi of interpretation that determinate significantly the meaning of dīn, millah and syarī’ah and how they are related. The one that uses the relation of synonymy avoid ta’ārud al-adillah reading (the dispute among axioms) so leads to inclusive comprehension. The other using the relation of hyponymy between din and syarī’ah leads to ta’arud reading, uses of nasikh wa al-mansūkh method (abrogation), and so leads to exclusive comprehension.